Defining the temporal relationship between the skin microbiome, immune response and skin barrier function during flare and resolution of atopic dermatitis: protocol of a Danish intervention study - Rønnstad, Amalie Thorsti Møller; Bay, Lene; Ruge, Iben Frier; Halling, Anne-Sofie; Fritz, Blaine Gabriel; Jakaša, Ivone; Luiten, Rosalie; Kezic, Sanja; Thomsen, Simon Francis; Bjarnsholt, Thomas; Thyssen, Jacob P. (BMJ open, 2023)
IntroductionLesional skin of atopic dermatitis (AD) is often colonised by Staphylococcus aureus and the bacterial abundance increases during a flare. However, the role of S. aureus and the skin microbiome in the pathogenesis of AD, including its influence on the dysfunctional skin barrier and immune response, remains to be elucidated. In this study, the temporal relationship between alterations in the skin barrier function, inflammation and microbiome is examined in adults with AD.Methods and analysisThis clinical study consists of 81 adult patients with AD, as defined by the Hanifin and Rajka criteria, and 41 age and sex-matched controls. The objectives are to examine alterations in the skin microbiome, skin barrier and immune response during (1) an untreated AD flare, (2) an AD flare treated with topical corticosteroids (TCS), (3) an AD flare treated with systemic dicloxacillin/placebo and TCS or (4) cutaneous exposure to either autologous S. aureus, staphylococcal enterotoxin B or a vehicle. Skin biopsies, tape strips, skin and nasal swabs are collected and analysed using RNA sequencing, multiplex immunoassays, liquid chromatography-mass spectrometry and 16S rDNA. Blood samples are analysed for filaggrin gene mutations and leucocyte gene expression.Ethics and disseminationThe scientific Ethical Committee of the Capital Region in Denmark (phases I and II: H-20011047, phases III and IV: H-21079287), the local data protection agency (phases I and II: P-2020-165, phases III and IV: P-2022-250) and the Danish Medicines Agency (phases III and IV: EudraCT 2021-006883-25, ClinicalTrials.gov: NCT05578482) have approved the studies. Participants will give written informed consent prior to study initiation. The study is conducted in accordance with the Helsinki Declaration. Outcomes will be presented at national and international conferences and in international peer-reviewed publications.Trial registration number NCT05578482, EudraCT 2021-006883-2.